ANALISIS RISIKO PADA RENCANA PEMANFAATAN MATA AIR METAUM DI DESA MARGA KABUPATEN TABANAN - Putra, Ketut Asmara; Norken, I Nyoman; Harmayanti, Kadek Diana (JURNAL SPEKTRAN, 2018)
One of the strategies to fulfil the needs of raw water in Tabanan is to plan for utilization of Wellspring of Metaum as a source of raw water. Before deciding to take the spring water source of Metaum as raw water, it was indicated the potential failure of either the pre-construction, the construction and the post-construction for example in the management of groundwater abstraction permits and the determination of trace pipeline network. The risk analysis was conducted on the plan to use the Wellspring of Metaum in Marga village of Tabanan, descriptive and qualitative methods. Data were collected through questionnaires that distributed to 28 respondents based on purposive sampling method. The result showed that there were 44 risks in the utilization plan of Wellspring of Metaum. These included 14 unacceptable risks, 24 undesirable risks and 6 acceptable risks. This indicated that the utilization of Wellspring of Metaum has a high level of risks, especially for the unacceptable categories and the undesirable risk categories. The mitigation actions that should be performed were dissemination and lobbying to the religious leaders / people directly affected as well as a limitation of protection for the sacred area. While mitigation action for the undesirable risks can be conducted through dissemination and personal approach through district level officials, village or neighborhood small units directly affected. The risk ownerships of the unacceptable risks were the Local Government / Central Office / Central River Region of Bali-Penida, Consultant / Contractor and the people. For the risk taker of the undesirable risk category are the Local Government / Central Office / Central River Region Bali-Penida, Consultant / Contractor and the people. Keywords : risk analysis, Wellspring of Metaum, Mitigation, Risk Ownerships.